Integrating Islamic values into waste management: Efforts to raise environmental awareness from an early age through guidance on memorizing short hadiths at MDTA Al-Falah, Hamlet 2, Neglasari Village - Nunung Nursyaidah; Tajul Muttaqin; Dyah Wulandari (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Waste management is an increasingly urgent problem amidst public awareness of the importance of cleanliness and environmental sustainability. One approach that can be implemented to overcome this problem is to integrate Islamic values in education from an early age, especially through teaching that involves memorizing short hadiths. This research aims to explore the application of Islamic values in waste management in educational environments, especially at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Al-Falah Dusun 2, Neglasari Village. The approach used is qualitative with observation and interview techniques with teachers, parents and students at MDTA Al-Falah. Through a program to memorize short hadiths related to cleanliness, such as the hadith which states